2012
DOI: 10.1080/17457300.2011.603426
|View full text |Cite
|
Sign up to set email alerts
|

Child injury prevention in Vietnam: achievements and challenges

Abstract: As with other South Asian countries, injury is becoming a leading cause of death and morbidity among children in Vietnam. In response to the increasing burden of child injury, government and non-government agencies in Vietnam have combined efforts during the last decade to develop and implement various child injury prevention strategies and programmes. This article provides, through a review of relevant documents and interviews with major stakeholders, an overview of these efforts and highlights major challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Some middle–income countries, such as Viet Nam, have already moved towards tackling childhood unintentional injuries systematically, though specific policies. The establishment of a National Policy on Injury Prevention has resulted in an increased awareness to the problem of unintentional injuries in children in Viet Nam and has given some direction for preventative efforts [ 25 ]. Educational campaigns, swimming lessons, legislation and enforcement of helmet wearing for the population aged over 6 years and creating safer homes, schools and community environments have all been implemented to some degree throughout the country [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some middle–income countries, such as Viet Nam, have already moved towards tackling childhood unintentional injuries systematically, though specific policies. The establishment of a National Policy on Injury Prevention has resulted in an increased awareness to the problem of unintentional injuries in children in Viet Nam and has given some direction for preventative efforts [ 25 ]. Educational campaigns, swimming lessons, legislation and enforcement of helmet wearing for the population aged over 6 years and creating safer homes, schools and community environments have all been implemented to some degree throughout the country [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that injuries in children are preventable through the combination of education, legislation and enforcement, environmental modifications, and promotion of safer products and safety devices. 59 Recognition of an "epidemiologic transition" in LMICs from acute infectious diseases and malnutrition to injuries as a leading cause of mortality is important. 60 Key to decreasing the morbidity and mortality associated with childhood injuries is the concept of injury control.…”
Section: Preventionmentioning
confidence: 99%
“…In Vietnam for example, significant inroads have been made in raising community awareness about injury prevention and legislation mandating helmet use by all riders and passengers on motorcycles has the potential to decrease morbidity and mortality in a country where these are the principal mode of transportation. 59 The Road Safety in 10 Countries project has made some progress in reducing injuries from RTI in the countries involved. 60 In Bangladesh, the Saving of Lives from Drowning project aims to reduce the high burden of childhood drowning and is one of the largest childhood-drowning-prevention projects ever undertaken in LMICs.…”
Section: Preventionmentioning
confidence: 99%
“…Recognizing the huge burden of such loss, the United Nations launched an initiative in 2011 called a ‘Decade of Action for Road Safety’ with the aim of stabilizing and then reducing global road deaths by 2020 (1). With dramatic economic growth and the improvement of living standards, Vietnam has experienced a rapidly growing number of motor vehicles on its roads in recent years; however, motorcycles still represent the main mode of transport with 26,869,025 motorcycles registered in 2010 (2). The pattern of unintentional injury of adolescents and young adults in Vietnam had previously been periodically studied in several surveys.…”
mentioning
confidence: 99%
“…However, no in-depth analysis has been performed specifically for motorcycle riding, helmet use and prevalence of RTI by demographic characteristics, particularly the risk factors associated with RTI among Vietnamese youths. This paper (1) compares the prevalence of motorcycling, helmet use and prevalence of RTI among youths in Vietnam in 2004 and again in 2009 and (2) determines the risk and protective factors associated with RTI among Vietnamese youths.…”
mentioning
confidence: 99%